2012
DOI: 10.1142/s0218301312500474
|View full text |Cite
|
Sign up to set email alerts
|

The Quest for the Heaviest Uranium Isotope

Abstract: We study Uranium isotopes and surrounding elements at very large neutron number excess. Relativistic mean field and Skyrme-type approaches with different parametrizations are adopted in the study. Most models show clear indications for isotopes that are stable with respect to neutron emission far beyond N=184 up to the range of around N=258.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…This has been demonstrated, e.g. in [2], where it was shown that the drip point for the example of uranium isotopes varies by more than 70 neutrons, looking at a range of standard Skyrme and relativistic mean field (RMF) approaches. Fig.…”
Section: Introductionmentioning
confidence: 91%
“…This has been demonstrated, e.g. in [2], where it was shown that the drip point for the example of uranium isotopes varies by more than 70 neutrons, looking at a range of standard Skyrme and relativistic mean field (RMF) approaches. Fig.…”
Section: Introductionmentioning
confidence: 91%
“…Here one can also see the stability peninsula at N=258. This magic number was discussed in [4]. Fig.…”
mentioning
confidence: 87%
“…From the experimental side, the picobarn ranges of cross sections for production of these nuclei provide limited structural information. On the other hand, the α-decay chains of nuclei synthesized in experiments using a 48 Ca beam with actinide targets are stopped by spontaneous fission before reaching the known region of nuclear chart.…”
Section: Introductionmentioning
confidence: 99%